The effects of SNAI1 rs6125849 gene polymorphism on metastasis and survival in colorectal cancer: Preliminary results from Turkish subjects - SÜSLEYİCİ, BELGİN (ELSEVIER, 2021)
Background: Since metastasis is one of the leading causes of high mortality in colorectal cancer, uncovering the molecular mechanisms underlying metastatic process has become important to find new treatment approaches. With this perspective, in this study we investigated effects of epithelial-mesenchymal transition (EMT) inducer SNAI1 rs6125849 gene polymorphism on different features of colorectal cancer. Material and methods: A total of 141 Turkish subjects consisting of 72 colorectal cancer patients and 69 healthy controls were included in the study. SNAI1 rs6125849 genotype analyses were performed with Agena MassARRAY platform. Results: We did not find any significant difference between case and control groups for rs6125849 genotypes. All metastatic patients were detected to have homozygous mutant (AA) genotype. Heterozygous and homozygous mutant genotypes (GA + AA) were more common in metastatic colorectal cancer patients compared to those with homozygous wild type (GG) genotype (p = 0.066). We also detected positive, albeit low but significant correlation between rs6125849 genotypes in codominant and dominant models (r = 0.250, p = 0.034 and r = 0.234, p = 0.048, respectively). Overall survival times was found to be considerably higher patients with A allele (Log rank: 3.04, p = 0.081). Conclusion: According to our preliminary results, we may speculate that SNAI1 gene G > A variation may result with a metastatic phenotype and shorter overall survival. Due to limited number of patients in our study group, further in vitro and in vivo studies are required to understand the role of SNAI1 rs6125849 variation on metastasis and survival functions.
Keywords: SNAI1; rs6125849; Colorectal Cancer; Gene polymorphism; Metastasis; EPITHELIAL-MESENCHYMAL TRANSITION; E-CADHERIN EXPRESSION; TRANSCRIPTIONAL REPRESSOR SNAIL; TUMOR-GROWTH; BREAST-CARCINOMA; EMT; INVASION; PROGRESSION; ALLIANCE; DOMINANT